Leadership Support and Employee Creativity: A Meta-Analysis - Wajdi, Farid (Jurnal Optimasi Sistem Industri, 2018)
Leaders who have transformational, empowerment, and other positive characteristics positively affect the performance of employee creativity. This study aimed to confirm and clarify the influence of leadership on employee creativity through meta-analysis method. Thirty-two titles of articles with 33 studies used in the analysis, yielding correlation values that support the hypothesis (0.27). In a geographical perspective, there is no difference between the west and the east. This can be seen from the comparable correlation value of each 0.268 and 0.274. However, in a sectoral perspective, manufacturing firms have a more prominent correlation (0.322) than service firms or mixed (0.238 and 0.235). Different motivation factors need to be considered as the link between personal and contextual factors. Therefore, further research should be done to examine the role of different motivations in linking the leadership support on employee creativity.